Some current manifestations of native music in Sonora, México - Ferrales Nápoles, Marybel (UNIVERSIDAD DE SONORA, 2021)
The richness of the indigenous musical tradition in Sonora lies in the variety and meanings constituting an important factor in the identity of their towns. However, the research about the music of the native cultures on the region are only a few; therefore, it is necessary a study focusing the meaning as a collective cultural phenomenon and his musical analysis. The objective of this work is releasing information of how music is currently manifested today in some ethnic groups of Sonora through transcriptions and analysis of representatives works. It began by collecting auditory and visual evidence of indigenous music that has reached our days as a product of a historical process in different ethnic groups in the State of Sonora. Five works were selected from own recordings or provided by Lutiscu (2007), which were transcribed and accompanied with a short description of the context where they are interpreted and its melodic, harmonic, formal and metric analysis; as well as the accompaniment, intonation and timbre of voices. It concludes that contemporary indigenous music performed in the Sonoran territory it is a transmitter of the actual thoughts of the ethnic groups; in many cases, rebuilding old parameters to shape current generations and not interpreting itself outside the local context.